THE EXPERIENCE OF INFLIXIMAB USAGE IN JUVENILE ARTHRITIS IN THE REPUBLIC OF BASHKORTOSTAN - V. A. Malievskii; G. R. Gareeva; D. D. Prolygina; E. P. Pervushina; A. Zh. Nuriakhmetova; L. F. Yalaeva ("Paediatrician" Publishers LLC, 2012)
The experience of infliximab usage in juvenile arthritis treatment in the Republic of Bashkirtostan is summarized in this article. Fourteen children (6 boys and 8 girls) at the age of 5,0-19,4 years old were included into the study. The mean single dosage of the drug 5,5+1,2 mg/kg per infusion according to the standard scheme 0-2-6 weeks, then every 8 weeks. The duration of the treatment varied from 0,2 to 2,0 years. The primary inefficiency of the drug was noted in only 1 case (7,1%), in 5 patients (35,7%) the treatment was arrested due to the secondary inefficiency, which developed in 0,9-1,5 years after its beginning. Allergic anaphylactoid reactions at the 10th and 14th infusions caused the drug withdrawal in 2 children (14,3%). In one year the treatment was completed in 9 patients (64,3%). The positive effect (improvement on at least 30% according to the ACRpedi criteria) in 2 weeks after the 1st infusion was registered in the majority of the patients (12 of 14 children, 85,7%). In 6 months of the treatment the improvement was achieved in all patients who continued to receive the drug. By the end of the 1st year of the treatment secondary inefficiency was found in 2 of 9 children, who continued to receive the drug; 5 patients had medicinal remission.